The Effects of Varying Dietary Protein Levels on Growth Performance of the Mekong River Catfish Pangasius Hypophthalmus Fries - Heng, Ngan (1999)
Seven practical diets were formulated to evaluate the growth, survival rate, body composition and nutrient gain of the Mekong River catfish Pangasius hypophthalmus fries under different dietary protein levels and protein to energy ratios. The diets contained 1 5 .76, 20.08, 24.3 6, 28.69, 3 3 .0 1 , 37.33 and 4 1 .63% protein and protein energy (P:E) ratio of 5 8 .0, 70.7, 82.0, 94.0, 1 05 .0, 1 1 4.0 and 1 23 . 0 mg/Kcal respectively. The experimental fish ranged 2.64 g - 2.75 g were nursed in twenty one 1 m3 hapas which were installed in a 600 m2 earthen pond at a stocking density of 1 5 fishes/hapa. All treatments were assigned at random and triplicated. Fish were fed at 1 0% of the total body weight daily for 90 days. Fifty percent of fish were sampled every fortnight for total length and weight However, on termination of the experiment, individual fish weight and length were recorded. Fishes fed with diets containing 3 3 .0 1 , 37.33 and 4 1 .63% protein showed significantly higher growth (p<0.05) than fish receiving diets containing 1 5 . 76, 20.08, 24.36 and 28.69% protein. The highest growth was recorded in fish fed with diet containing protein 37.33% and P:E 1 1 4mg/Kcal while the lowest growth was observed in fish fed with diet containing 1 5 . 76% protein. However, fish fed with diets containing 4 1 .63% and 1 23 mg/Kcal did not perform as well as fish fed with diet containing 37.33% protein. The fish growth rate increased significantly (p<0.05) with increasing dietary protein levels up to 3 7.3 3%. The growth rate decreased as the dietary protein was increased beyond 3 7 . 3 3% protein level. There was significantly positive correlation between specific growth rate (% per day) and protein to energy (P:E) ratio with an equation of Y= 0.6512 + 0.0055 X, r = 0.95 3 3 . I n conclusion, formulated diet containing 37.33% protein level, 3270 Kcal/Kg of energy and P:E ratio of 1 1 4 mg/Kcal favour maximum growth (24 1 3%), highest survival rate ( 1 00%), high protein gain (25 76%), and feed conversion ratio (3 .64) for Pangasius hypophthalmus fries.